Struggling for a transnational right to land norm - Laura Gerken (University of Duisburg-Essen, Käte Hamburger Kolleg / Centre for Global Cooperation Research (KHK/GCR21), 2023)
The right to land is increasingly recognized in transnational governance. In this paper, I argue that it has been established as a transnational norm. This argument is presented by tracing the transnational governance of land over time. I identified four phases that land governance progressed through. Initially, the issue of land was only indirectly included, while later on rights and regulations dealing specifically with land emerged, until the right to land finally became an established norm. It recognizes the crucial role of land for rural lives and livelihoods, grants individuals and communities a right to the land they are using, and protects them from dispossession. With the examples of the Voluntary Guidelines on the Responsible Governance of Tenure of Land, Fisheries and Forests (FAO 2012) and the Declaration on the Rights of Peasants and Other People Working in Rural Areas (UNGA 2018), I trace the role of social movements in the creation processes of both regulations. I argue that the growing market of land on a large scale in the mid-2000s led to the necessity of its regulation as a double movement. Due to the accompanying salience, social movements took political opportunities, to struggle for the recognition of a right to land. Because of past efforts of those movements, they provided expertise in this context. By closely connecting their claims to already established norms, the movements increased the likelihood of adopting the transnational right to land norm.
urn:nbn:de:hbz:465-20240502-122534-3
Keywords: 320; Norm Emergence; Large-Scale Land Acquisitions; Social Movements; Transnational Governance; Land Rig